МИКОЛА РЕРІХ ПРО РОЛІ ОСВІТИ В ФОРМУВАННЯ ОСОБИСТОСТІ ВЧИТЕЛЯ (Педагогіка вищої та середньої школи, 2008)
In the article an author exposes the pedagogical ideas o  Nick Rerih. Basic attention applies on the role of education in forming of growing personality. Three major aspects are selected: state of education in a country, role of school and teacher in education, relation of the state to the teacher as the transmitter of common to all mankind values.